2023
DOI: 10.1007/s11892-023-01498-z
|View full text |Cite
|
Sign up to set email alerts
|

Weight Regain After Bariatric Surgery: Scope of the Problem, Causes, Prevention, and Treatment

Abstract: Purpose of Review Although bariatric surgery is the most effective treatment of severe obesity, a proportion of patients experience clinically significant weight regain (WR) with further out from surgery. The purpose of this review is to summarize the prevalence, predictors, and causes of weight regain. Recent Findings Estimating the prevalence of WR is limited by a lack of consensus on its definition. While anatomic failures such as dilated gastric fundus after sleeve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 64 publications
(23 citation statements)
references
References 135 publications
0
15
0
Order By: Relevance
“…4,5 However, 11% to 22% of patients experienced suboptimal weight loss within the first 2 years after surgery, and 10% or greater weight regain was reported by 23% and 72% of patients at 1 year and 5 years after surgery, respectively. 6 Weight regain is a major challenge facing bariatric teams. A systematic review identified 5 categories of risk factors associated with weight regain: temporal, anatomical, genetic, dietary, and psychiatric factors.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…4,5 However, 11% to 22% of patients experienced suboptimal weight loss within the first 2 years after surgery, and 10% or greater weight regain was reported by 23% and 72% of patients at 1 year and 5 years after surgery, respectively. 6 Weight regain is a major challenge facing bariatric teams. A systematic review identified 5 categories of risk factors associated with weight regain: temporal, anatomical, genetic, dietary, and psychiatric factors.…”
Section: Introductionmentioning
confidence: 99%
“…7 Furthermore, an additional review suggested that the most common factors associated with weight regain were dysregulated or maladaptive eating behaviors, lifestyle factors, life stresses, and depressive symptoms. 6 Data from systematic reviews and meta-analyses concluded that post-bariatric surgery eating psychopathology was associated with weight regain 8 and showed an association between depression and disordered eating, lower mental quality of life, and weight regain. 9 Given that weight regain has been associated with recurrence of medical comorbidities and deterioration in quality of life, 6,10,11 developing efficacious psychosocial interventions that target risk factors and prevent or reverse weight regain is imperative.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations